The impact of channel conflict on channel efficiency : the case of Portuguese water heaters producers and distributors - Soares, Jorge Manuel Lourenço (2014)
The focus of this paper is to examine the relationship between channel conflict and channel efficiency. For that purpose, this paper compares the early distribution literature and the industrial network approach. The research strategy adopted is action research, including participant observation by the author. In addition, direct intervention was taken from the parties involved (producer, wholesalers and retailers) in order to present some facts and considerations to the phenomena under study. This paper endeavors to provide a contribution to the theory of channel distribution, as it presents an attempt to investigate channel conflict theories applied to the distribution channel of water producers. It attempts to offer a contribution to the study of channel efficiency, as it delivers, based on the literature review, some ideas to a producer that has to manage, on a daily basis, the efficiency of its channel distribution.